The Effects of Flecainide Acetate on Inflammatory-Immune Response in Lipopolysaccharide-Stimulated Neutrophils and on Mortality in Septic Rats - Chung, Shi Young (Acute Crit Care, 2018)
BACKGROUND: Flecainide acetate is a drug used primarily for cardiac arrhythmia. Some studies also imply that flecainide acetate has the potential to regulate inflammatory-immune responses; however, its mechanism of action is contended. We determined the effects of flecainide acetate on lipopolysaccharide (LPS)-stimulated human neutrophils in vitro and on mortality in a septic rat model. METHODS: Neutrophils from human blood were cultured with varying concentrations of flecainide acetate (1 μM, 10 μM, or 100 μM) with or without LPS (100 ng/ml). To assess neutrophil activation, the protein levels of tumor necrosis factor-alpha (TNF-α) and interleukin (IL)-6 and IL-8 were measured after a 4-hour culture period. To assess the intracellular signaling pathways, the levels of phosphorylation of p38 mitogen-activated protein kinase (p38), extracellular signal-regulated kinase (ERK) 1/2, and c-Jun N-terminal kinase (JNK) were measured after a 30-minute culture period, and the nuclear translocation of nuclear factor (NF)-κB was measured after a 1-hour culture period. Additionally, the survival rate was investigated in a rat sepsis model. RESULTS: Flecainide acetate down-regulated the activation of proinflammatory cytokines, including TNF-α and IL-6 and IL-8, and intracellular signaling pathways including ERK 1/2 and NF-κB. Flecainide acetate also improved the survival rate in the rat sepsis model. CONCLUSIONS: Collectively, these findings indicate that flecainide acetate can improve survival in a rat sepsis model by attenuating LPS-induced neutrophil responses. We therefore suggest that flecainide acetate plays an important role in modulating inflammatory-immune responses.